What is the prevalence of dyslipidemia in patients with idiopathic tinnitus? - Erdogdu, Suleyman (International Journal of Research in Medical Sciences, 2020)
Background: Dyslipidemia is a metabolic disorder that results from imbalanced and overfeeding as well as sedentary life. Elevated blood lipid levels can affect cochlear blood flow and fluidity, leading to decreased hearing and tinnitus. We aimed to determine whether there is a relationship between tinnitus and dyslipidemia by investigating the blood lipoprotein values of patients with tinnitus. Methods: The lipid profiles of the patients with idiopathic tinnitus who were selected among the patients who applied to Istanbul Haydarpaşa Numune Training and Research Hospital with the complaint of tinnitus between January 2019 and May 2020 were examined. The test results and age and gender distributions were compared with control groups without tinnitus complaints and statistical evaluation was performed. Results: Hypercholesterolemia in 42% of 6472 patients with idiopathic tinnitus, 18% low HDL, 50% high LDL, Hyperlipidemia was detected in 21%. 1942 (30%) of these patients were male; 4530 (70%) are women. The number of patients in the control group without tinnitus was 6470. Hypercholesterolemia in 49% of this group; 21% low HDL, 42% high LDL, 16% hyperlipidemia was detected. In this control group, 1950 (30%) of the patients were male and 4520 (70%) were female. Cholesterol of male and female patients with tinnutus. When the cholesterol, LDL and triglyceride values of HDL and LDL values and female and male patients in the control group were examined, a statistically significant difference was found (p <0.005). No statistically significant difference was found between HDL values of female and male patients with tinnutus and HDL values of female and male patients in the control group (P> 0.05). Conclusions: There is a statistically relationship between tinnitus and dyslipidemia. The presence of dyslipidemia is vital due to atherosclerosis caused by dyslipidemia, especially coronary artery involvement. Therefore, dyslipidemia should be treated as it causes many diseases.